2018
DOI: 10.1080/10942912.2018.1514631
|View full text |Cite
|
Sign up to set email alerts
|

Chemical composition and antioxidant activity of quince fruit pulp collected from different locations

Abstract: This study was carried out to examine the physicochemical and functional characteristics of quince fruit pulp. The matured quince fruits were collected from different locations of Poonch, AJ&K, Pakistan. Significant differences (P ˂ 0.05) were found among fruits collected from these locations. The quince pulp has the following characteristics: pH (3.43), total soluble solids (14.22°Brix), acidity (1.25%), carbohydrate (13.38 g/ 100 g), reducing sugar (5.15 g/100 g), non-reducing sugar (4.61 g/100 g), moisture … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 16 publications
0
18
1
1
Order By: Relevance
“…It is a significant dietary source of essential phytochemicals including phenolic acids and flavonoids 106 . In Pakistan, Rahman et al, 49 and Rasheed et al, 72 investigated the antioxidant activity of C. oblonga. An attempt from Chitral valley of Pakistan performed DPPH scavenging assay of C. oblonga crude ethanol extract that validated maximum activity of 27.18% at 500µg/ml and minimum activity 9.70% at 100µg/ml.…”
Section: Cydonia Oblonga (Quince)mentioning
confidence: 99%
See 1 more Smart Citation
“…It is a significant dietary source of essential phytochemicals including phenolic acids and flavonoids 106 . In Pakistan, Rahman et al, 49 and Rasheed et al, 72 investigated the antioxidant activity of C. oblonga. An attempt from Chitral valley of Pakistan performed DPPH scavenging assay of C. oblonga crude ethanol extract that validated maximum activity of 27.18% at 500µg/ml and minimum activity 9.70% at 100µg/ml.…”
Section: Cydonia Oblonga (Quince)mentioning
confidence: 99%
“…The mature fruits of C. oblonga collected from different locations of Poonch AJK Pakistan evaluated for physicochemical analysis revealed presence of certain compounds and essential nutrients. The phenolic content (gallic acid) present in fruit of this plant possesses potential antioxidant 72 .…”
Section: Cydonia Oblonga (Quince)mentioning
confidence: 99%
“…Bystrická et al (2017) reported that the content in phytochemical compounds, beside the variety, may be affected by many factors, also climatic conditions, the agrochemical composition of the soil and the maturity index (Blanda et al, 2020). Rasheed et al (2018) reported on the composition of quince fruit pulp collected from different locations and concluded that there is a great variation in chemical composition among the fruits from different localities. These changes are attributed to differences in the environmental conditions and the soils.…”
Section: Introductionmentioning
confidence: 99%
“…Quince (Cydonia oblonga Miller) is a climacteric pome fruit that belongs to the Rosaceae family (Benzarti et al, 2015;Hussain et al, 2019). It is a round or pear-shaped fruit with yellow skin and a sour and bitter taste but at the same time is really aromatic (Rasheed et al, 2018). Quince fruits have an important nutritional content as they are a rich source of organic acids, sugars, fibres and minerals.…”
Section: Introduction Introduction Introduction Introductionmentioning
confidence: 99%
“…Additionally, they also contain compounds with functional and antioxidant features, being the phenolic compounds the most important. Consumption of quince fruit have been related with health due to their hypoglycaemic action, antiinflammatory, antimicrobial and anticancer activities (Leonel et al, 2016;Rasheed et al, 2018).…”
Section: Introduction Introduction Introduction Introductionmentioning
confidence: 99%